An Analysis on Derivational Morphemes in the Joe Biden’s Inauguration Speech - Yuliani, Ummi; Regina; Susilawati, Endang; Sudarsono; Suhartono, Luwandi (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research aims to identify the most dominant type of derivational morphemes and the formation process of derivational morphemes found in the Joe Biden’s inauguration speech. This research was a descriptive study. The researcher used documents to collect the data. The corpus of this research was the transcript of the inauguration speech by Joe Biden. The data were collected from the official website “The White House”. Then, the data were sorted out of the corpus. This research used open coding and focused coding to analyze the data. The writer used the theory of Fromkin, Rodman, and Hyams to analyze the most dominant type of derivational morphemes and Koltai’s theory to analyze the formation process of derivational morphemes. The findings of this research found that the most dominant type of derivational morphemes found in the Joe Biden’s inauguration speech are suffixes with 147 data out of 158 data. The formation processes of derivational morphemes found are noun formation, verb formation, adjective formation, and adverb formation. Noun formation becomes the most dominant formation process with 107 data out of 158 data. This research covered two types of derivational morphemes and four formation processes of derivational morphemes as a discussion for further linguistic study on morphology, especially derivational morphemes.